Penerapan Metode Eksperimen dalam Pembelajaran Ilmu Kimia di SMU - Agus Abhi Purwoko (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
This classroom action research was designed to improve the quality of teaching-learning process in chemistry at class 2 of SMUN 1 Mataram. Observation, evaluation, and analysis of teaching-learning process were conducted during the implementation of the planned experimentation in the classroom or laboratory. The results showed that the quality of teaching-learning process improved. The students' enjoyment in learning chemistry and their awareness of its importance in their daily life increased. Besides, both students' average scores and comprehension also increased.